An Association of Fear of Childbirth with the Preference for Cesarean Section; A Cross Sectional Study - Ansari, Asma; Irum, Samina (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the fear of childbirth (FOC) amongst pregnant women and its association with preference for cesarean section.Study Design: Cross-sectional study.Place and Duration of Study: Department of Obstetrics and Gynecology Pak Emirates Military Hospital, Rawalpindi from Jan 2018 to Jun 2018.Methodology: Demographic and reproductive data of the patients including mode of delivery, was noted. The intensity of fear of childbirth was measured by Wijma delivery expectancy/experience questionnaire (W-DEQ), and a score was allotted. The total sum of scoring ranged from 0 to 165. A score of >85-99 indicated an intense fear of childbirth, and ≥100 indicated very intense fear. The frequency of requests for cesarean section in women suffering from fear of childbirth was calculated.Results: A total of 335 patients were included. The mean age was 28.74 ± 3.58 years, and the mean gestational age was 39.50 ± 1.43 weeks. The mean W-DEQ score was 94.59 ± 9.86. The fear of childbirth calculated by W-DEQ in the third trimester of pregnancy showed no fear in 233 (69.55%) participants, intense fear in 42 (12.54%) and very intense fear in 60 (17.91%) women. The requests for cesarean section in women suffering from intense fear were made by 5 (11.90%) women and in women suffering from very intense fear of childbirth was 19 (31.67%) (p-value